Reconstructing Immersive Spaces by Contemporary 3D Scanning Workflows (EAAE Annual Conference Proceedings, 2023)
Shaping the ideal scan-to-BIM (Building Information Modeling) workflow has been an ongoing goal in the Architecture, Engineering, Construction and Facility Management (AEC/FM) domains. This innovative workflow autonomously processes raw data to usable 3D models for virtual environments that can be directly utilized. In this case study, several reconstruction techniques were explored such as a highend laser scanner as well as a relatively low-cost LiDAR integrated Tablet.